Poor outcome of patients with pulmonary arterial hypertension with insufficient response to phosphodiesterase-5 inhibitors alone or in combination with other specific therapy: a registry-based study. (September 2020) - Hjalmarsson, Clara; Butler, Oisin; Hesselstrand, Roger; Holl, Katsiaryna; Jansson, Kjell; Klok, Rogier; Rådegran, Göran; Söderberg, Stefan; Kjellström, Barbro
Phosphodiesterase-5 inhibitors are commonly used in pulmonary arterial hypertension but, as suggested by the RESPITE study, phosphodiesterase-5 inhibitor therapy (mono-/combination) does not always have a satisfactory treatment effect. This study aimed to investigate the clinical course of pulmonary arterial hypertension patients not at treatment goal after at least 90 days of treatment with phosphodiesterase-5 inhibitors, alone or in combination with other pulmonary arterial hypertension therapies. The study included 106 incident patients from the Swedish Pulmonary Arterial Hypertension Registry, treated with phosphodiesterase-5 inhibitors for ≥90 days, who were not at a pre-specified treatment goal, i.e. in World Health Organisation functional class III, with 6-min walking distance 165–440 m, and N-terminal prohormone of brain natriuretic peptide >300 ng/L. Changes in World Health Organisation functional class, 6-min walking distance, N-terminal prohormone of brain natriuretic peptide, and risk group between index and follow-up were assessed. Of patients with complete follow-up data, ( n = 53) 77% were on combination therapy and risk assessment yielded 98% at intermediate risk at index. At follow-up, 11 patients transitioned from World Health Organisation functional class III to World Health Organisation functional class II, the median (Q1; Q3) change in 6-min walking distance was 6 (−30; 42) meters and in N-terminal prohormone of brain natriuretic peptide 47 (−410; 603) ng/L, while 89% remained at an intermediate risk. Of those without complete follow-up data, 11 patients died and 2 underwent lung transplantation. In conclusion, pulmonary arterial hypertension patients treated with phosphodiesterase-5 inhibitors, as single or combination therapy and not achieving the pre-specified treatment goals after ≥90 days have an unfavourable clinical course.